Developing Intellectual Property Character for Games to Teach Music Theory by Using Batik Patterns Inspiration - Ahmad Faisal Choiril Anam Fathoni; Jehezkiel Christian Ray (Humaniora, 2020)
The research aimed to apply batik motifs to strengthen the differentiation of characters in the form of adventure games that could be an interesting and effective learning medium for introducing music theory. In order to work towards achieving its objective, developing interest in music theory by using games and animations specifically to approach more people and make this project sustainable, these games were supposed to be aimed into intellectual property. Therefore to be able to make it competitive, strong differentiation was needed as so many IP characters emerged as competitors. One of the strengths that could be added to these characters was by applying local content. It was a strong differentiator and could be developed with a deeper philosophy so that it had a wealth that could be developed more widely in the future, which in this case was using batik. To achieve goal, the research used the design thinking method and qualitative methodology to collect data. The researchers collected data through the process of document research, an observation about the implementation of batik patterns in character design for animation. The result is the characters’ designs of a game to teach music theory using batik pattern application. In conclusion, the batik pattern has the potential to strengthen differences in character design.